2019
DOI: 10.6026/97320630015439
|View full text |Cite
|
Sign up to set email alerts
|

Virtual screening of inhibitors against Envelope glycoprotein of Chikungunya Virus: a drug repositioning approach

Abstract: Chikungunya virus (CHIKV) a re-emerging mosquito-borne alpha virus causes significant distress which is further accentuated in the lack of specific therapeutics or a preventive vaccine, mandating accelerated research for anti-CHIKV therapeutics. In recent years, drug repositioning has gained recognition for the curative interventions for its cost and time efficacy. CHIKV envelope proteins are considered to be the promising targets for drug discovery because of their essential role in viral attachment and entry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Trajectories analyses were performed using the CPPTRAJ modules (Roe & Cheatham, 2013. Authors analyzed different trajectories like root mean square deviation (RMSD), a root mean square fluctuation (RMSF), hydrogen bonds (HBs) obtained from the MD simulation along with the change in binding free energy calculation using the AMBER18 (Agarwal et al, 2019;Al-Refaei et al, 2020;Cob-Calan et al, 2019;Nazarian et al, 2015;Pola et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Trajectories analyses were performed using the CPPTRAJ modules (Roe & Cheatham, 2013. Authors analyzed different trajectories like root mean square deviation (RMSD), a root mean square fluctuation (RMSF), hydrogen bonds (HBs) obtained from the MD simulation along with the change in binding free energy calculation using the AMBER18 (Agarwal et al, 2019;Al-Refaei et al, 2020;Cob-Calan et al, 2019;Nazarian et al, 2015;Pola et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Still, it hydrophobically interacts with Leu 42 , Val 179 , Tyr 180 , Asn 264 , Pro 265 , and Val 266 , while also interacting with Ser 120 and Tyr 122 amino acids, via hydrogen bonding interactions at distances of 2.07 and 2.1 Å, respectively ( Figure 9 C). Additionally, in silico studies involving E3-E2-E1 glycoproteins have been developed focusing on virtual screening of phenothiazines, bafilomycin [ 85 ], and FAD-approved antimicrobial agents, such as cefmenoxime, ceforanide, cefotetan, cefonicid sodium, and cefpiramide [ 86 ]. Recently, Song et al (2019) [ 87 ] reported the crystal structures of the free mouse MXRA8 (mMXR8) receptor and the complex between human MXRA8 (hMXRA8) and the CHIKV E3-E2-E1 glycoproteins complex.…”
Section: Resultsmentioning
confidence: 99%
“…The repurposing of several molecules/inhibitors has been reported like chloroquine (antimalarial drug), ribavirin, suramin, T-705, arbidol, chlorpromazine, imipramine, piperazine, and cephalosporin (anti-bacterial) to inhibit CHIKV [53][54][55]. Similarly, mycophenolic acid which is an immunosuppressant and anti-proliferative molecule can be repurposed for CHIKV as it can control 99.9% viral replication at a concentration of 10 μM [16].…”
Section: Drug Repurposingmentioning
confidence: 99%
“…Recently, Kumar et al exploited molecular docking and dynamic simulation studies and reported ribostamycin sulfate as an inhibitor of CHIKV nsP2 protease [59]. Moreover, Agarwal et al reported cephalosporin drugs targeting CHIKV E1-E2 proteins using drug repurposing and in silico approaches [53].…”
Section: Drug Repurposingmentioning
confidence: 99%